Sosialisasi Media Intraktif Menggunakan Canva Berbasis Artificial Intelligence (AI) di SMA Negeri 6 Maluku Tengah - Carolina Sri Athena Barus (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
This article discusses the socialization n of interactive media utilizing Canva, enhanced with Artificial Intelligence (AI), at SMA Negeri 6 Central Maluku. The initiative aims to modernize the educational tools available to teachers and students, promoting a more engaging and effective learning environment. Canva's AI-driven features facilitate the creation of dynamic and visually appealing educational content, making complex concepts easier to understand. The socialization process involved training sessions for teachers and interactive workshops for students, highlighting the practical applications of AI in education. The feedback from participants indicated a significant improvement in both teaching methodologies and student engagement. This project demonstrates the potential of AI-based tools in transforming traditional educational practices, paving the way for future innovations in the field of education.